(untitled) (Dissertation Nursing, 2025)
BACKGROUND: The nurse, part of the care team, plays a key role in the different stages of care and rehabilitation process of the person with spinal cord injury. Its role is carried out in the promotion, care and maintenance of the sexual health and well-being of the person with spinal cord injury. AIM: To explore nurses’ experiences regarding the sexual sphere of adult persons with spinal cord injury, especially by identifying facilitating or obstructive factors in addressing the dialogue with caregivers and the strategies used to promote their satisfaction. MATERIALS AND METHODS: It is intended to conduct a qualitative phenomenological descriptive study with convenience sampling. Individual face-to-face, semistructured, open-ended question interviews will be conducted with nurses on wards that receive people with myelopathic conditions. The content of the interviews will undergo coding and categorization according to the themes that emerged during the analysis using the Colaizzi method. EXPECTED RESULTS: The application of this research protocol will provide further information on the knowledge, approach, and disposition of a cohort of Italian nurses have regarding the sexual sphere of people with myelopathy. Lastly, it will be possible to identify the specific skills that are used for the fulfillment of this need if it is compromised.